2002
DOI: 10.1128/jb.184.3.621-628.2002
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes relAandhptMutants Are Impaired in Surface-Attached Growth and Virulence

Abstract: We describe here the identification and characterization of two Listeria monocytogenes (Tn917-LTV3) relA and hpt transposon insertion mutants that were impaired in growth after attachment to a model surface. Both mutants were unable to accumulate (p)ppGpp in response to amino acid starvation, whereas the wild-type strain accumulated (p)ppGpp within 30 min of stress induction. The induction of transcription of the relA gene after adhesion was demonstrated, suggesting that the ability to mount a stringent respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 38 publications
1
99
1
2
Order By: Relevance
“…In E. coli, the two proteins RelA and SpoT regulate the concentration of (p)ppGpp, a global transcriptional activator of numerous metabolic pathways under starvation conditions (19). RelA is important for the virulence of Listeria monocytogenes (20), for the activation of quorum sensing in Pseudomonas aeruginosa (21), and for long-term survival of Mycobacterium tuberculosis (22). In Brucella spp.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, the two proteins RelA and SpoT regulate the concentration of (p)ppGpp, a global transcriptional activator of numerous metabolic pathways under starvation conditions (19). RelA is important for the virulence of Listeria monocytogenes (20), for the activation of quorum sensing in Pseudomonas aeruginosa (21), and for long-term survival of Mycobacterium tuberculosis (22). In Brucella spp.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that the ability of bacteria to synthesize (p)ppGpp and mount a stringent response is an essential physiological adaptation required for stages of pathogenesis, such as initial growth of adherent bacteria [38], toxin production [39], motility [40] and expression of other virulence regulators [41]. Comparative analysis revealed that the IPAV spoT gene (LIF_A2491) has two missense mutations at the amino-acid residues, Val293 and Lys407, resulting in replacement by Ala and Glu, respectively.…”
Section: Mutations Affecting Genes Related To Stress Responsementioning
confidence: 99%
“…150,151 A L. monocytogenes mutant for relA, a gene encoding a (p)ppGpp synthetase, is unable to accumulate (p)ppGpp in response to amino acid starvation. 152 In addition to be required for full virulence in mice, RelA was shown to play a critical role for bacterial intracellular growth in non-phagocytic cells and macrophages. These results suggest that, after phagosomal escape, the capacity to mount a stringent response is pivotal for maximal Listeria intracellular replication.…”
Section: Monocytogenesmentioning
confidence: 99%